Income Shocks Reduce Human Capital Investments : Evidence from Five East European Countries - Dasgupta, Basab; Ajwad, Mohamed Ihsan (2012)
This paper empirically investigates whether households affected by income shocks cope by reducing human capital investments. The analysis uses Crisis Response Surveys conducted in Armenia, Bulgaria, Montenegro, Romania, and Turkey during 2009 and 2010. A propensity score matching technique is adopted to compare health and education investment decisions among households that were affected by income shocks to the matched comparison group. The authors find that households affected by income shocks reduced some human capital investments. Interestingly, households in these five countries were more likely to adopt health-related coping strategies as opposed to education-related coping strategies. The results from Armenia, Bulgaria, Montenegro, and Turkey show that households affected by income shocks reduced their visits to doctors and reduced their spending on medicine and medical care significantly more than the matched comparison group. Households affected by income shocks reduced their education investments, but did not adopt harmful education-related coping strategies, such as withdrawing children from schools or moving children from costly private to cheaper public schools. These findings reveal that long-term and possibly intergenerational household welfare could be affected by short-run income shocks and hence underscore the need for governments to employ mitigation measures.